Humic Acid Aplication in Catfish Farming Using Bucket System in Muncul Fish Farm, Banyuwangi, Indonesia - Darmawan Setia Budi; Hapsari Kenconojati; Mohammad Faizal Ulkhaq; Muhammad Yusuf Taufiqur Rohman; Shovia Finny Anggraeni; Farahnovita Yuliyanti; Ahmad Alie Fikri; Shierly Zaissiliya Clarissa Lifani; Hikam Zainul Qolbi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
In Banyuwangi, Indonesia, where the vast potential of natural resources remains largely untapped optimally, the community partnership program (CPP) was introduced to enhance freshwater fish production, with a specific focus on catfish farming in the Muncul fish farm. The region's catfish production, the largest among consumer fish commodities, had been hampered by traditional and semi-intensive methods, limited facilities, disease risks, and uncertain market conditions. To address these challenges, the CPP employed a participatory approach, fostering a close relationship between the community development team and partner groups. Through scientific problem-solving discussions, valuable input from partners, and active participation in decision-making, catfish farmers were empowered. The central innovation of applying humic acid in a bucket fish farming system significantly improved catfish productivity and profitability. As a result, partners gained knowledge and skills in intensive bucket fish farming, substantially increasing their productivity and income. To further expand the benefits of this program, promoting urban farming concepts, especially the bucket fish farming system, should be encouraged to engage more individuals with limited space in small-scale aquaculture for food security and income generation.